2012
DOI: 10.1590/s1516-35982012000100024
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de níveis de melão em substituição ao milho moído sobre o desempenho, o consumo e a digestibilidade dos nutrientes em ovinos Morada Nova

Abstract: Avaliaram-se o desempenho, o consumo e a digestibilidade aparente de componentes nutritivos em 32 ovinos Morada Nova em confinamento, 20 machos não-castrados e 12 fêmeas, recebendo dietas contendo 0, 30, 60 e 100% de melão em substituição ao milho moído. Os animais tinham em média 6 meses de idade, peso médio inicial de 15 kg e foram abatidos aos 25 kg. Utilizou-se delineamento experimental inteiramente casualizado, com quatro tratamentos e oito repetições. O consumo de MS apresentou tendência quadrática para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
1
7
0
9
Order By: Relevance
“…Rumen lactic acidosis is one of the major disorders and develops due to excessive ingestion of soluble carbohydrates by animals that are not adapted to such a diet as often occurs in intensive farming systems (Dunlop 1972, Dougherty et al 1975, Nagaraja & Titgemeyer 2007, Barrêto-Júnior et al 2008) . Due to the high availability and occasional surpluses of melon (Cucumis melo), this fruit has been used as an alternative feed source for sheep (Lima et al 2012) and has become an option for supplementing ruminants during food shortages in semi-arid northeastern Brazil (Araújo et al 2009, Lima et al 2011, Lima et al 2012, Oliveira et al 2015a. However, there is a lack of studies on the risks that accompany melon-induced acidosis in non-adapted animals.…”
Section: Introductionmentioning
confidence: 99%
“…Rumen lactic acidosis is one of the major disorders and develops due to excessive ingestion of soluble carbohydrates by animals that are not adapted to such a diet as often occurs in intensive farming systems (Dunlop 1972, Dougherty et al 1975, Nagaraja & Titgemeyer 2007, Barrêto-Júnior et al 2008) . Due to the high availability and occasional surpluses of melon (Cucumis melo), this fruit has been used as an alternative feed source for sheep (Lima et al 2012) and has become an option for supplementing ruminants during food shortages in semi-arid northeastern Brazil (Araújo et al 2009, Lima et al 2011, Lima et al 2012, Oliveira et al 2015a. However, there is a lack of studies on the risks that accompany melon-induced acidosis in non-adapted animals.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação ao desempenho dos ovinos alimentados com coproduto do abacaxi Neiva et al (2009) De toda a produção da fruta 70 % são comercializados no mercado nacional, regional e local, dentre as quais 20 % são destinadas a exportação e 10 % é considerado refugo (Costa et al, 2011b;Lima et al, 2012). O refugo é caracterizado como sendo a fruta que apresenta defeitos na sua aparência ou tamanho inadequado e, por isso, não pode ser comercializado como fruta fresca.…”
Section: Coprodutos Do Processamento De Frutas Tropicaisunclassified
“…Estudos realizados por Lima et al (2012) Avaliando o ganho de peso de borregos não-castrados, submetidos a quatro regime de manejo alimentar, Araújo et al (2009) encontraram resultados promissores e divergente do apontado por Lima et al (2012). Eles observaram que a substituição de 50 % da matéria seca do concentrado fornecido com base em 2 % do PV dia -1 , por coproduto de melão, não afetou o desempenho dos ovinos em estudo.…”
Section: Coprodutos Do Processamento De Frutas Tropicaisunclassified
“…The use of melons as a low cost alternative in animal feed has already been evaluated in sheep and cattle in animal production studies witch demonstrated the viability of this fruit as a partial replacement of energy-rich grains (LIMA et al, 2011(LIMA et al, , 2012. However, few studies report possible clinical changes of this supplementation.…”
Section: Introductionmentioning
confidence: 99%